MOTIVATION AND NEEDS FOR LEARNING A FOREIGN LANGUAGE AMONG STUDENTS OF TECHNICAL SCHOOLS (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This scientific article explores the application of mining terminology in a database, enhancing students' communicative competence. The high level of use of communicative forms of mining terminology, the active use of practical and theoretical experiments, has yielded scientific results. As is known, the primary goal of the student is to motivate students in the field of mining to take English lessons based on the tasks of the subject program. In addition, students engage in project-based learning, creating terms, which enables them to enhance their knowledge and skills by integrating their understanding of mining sciences with the mining industry and the English language. Improving students' knowledge and skills in mining in English is based on the principle of systematically selecting critical components of communicative competence, focusing on scientific topics and single-component and multi-component terms and expressions. Databases establish the extraction of terms from various mining texts and strengthen the development of a procedure for their interpretation.